English Translation of the Collection of Poems Drobtine iz mišje doline by Anja Štefan: Domestication and Foreignization in Nada Grošelj’s Translation - Kaloh Vid, Natalia; Koletnik, Mihaela (Trideset let literarne nagrade večernica, 2026)
One of the commonest challenges in translating children's literature is defining the extent to which the translator is allowed, or even required, to domesticate and adapt the text, as the translator's dilemma when selecting appropriate strategies is further complicated by the need to bring the original as close as possible to young readers. The concept of a »faithful translation« becomes even less significant in the translation of poetry, especially children’s poetry, since the purpose of translation is to recreate the poem in the target language while primarily preserving its rhyme and rhythm. The article focuses on the translation methods used by the famous Slovenian translator Nada Grošelj in her translation of Anja Štefan's award-winning children's poetry collection Drobtine iz mišje doline/Tunes from Mousedale Dunes, which received the Večernica Award in 2019. The aim of the analysis is to examine the translation solutions offered by translation into English, including the adaptation of personal names and culturally specific elements, as well as nursery rhymes and onomatopoeic expressions.